2012
DOI: 10.1080/15017419.2010.507376
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and coordination around children with individual plans

Abstract: In this article we discuss the relationship between cooperation and coordination around six children with special needs who attend Norwegian day care centres. The children in focus have 'individual plans', in which goals, roles and activities at the centre of the cooperation are documented, and are as such a coordinating device. Each child has a cooperative team consisting of parents, representatives from day care centre, the child's special educator, the public health nurse and, for instance, their physiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…This difference is notable because the coordinator is assigned the responsibility for the planning and follow-up for the ISP (Norwegian Directorate of Health, 2015). The discrepancy between reporting having a coordinator and the other types of coordinating services may be substantial; however, it could also be seen an under-reporting due to unclear boundaries and overlapping roles, for instance, when the child's physiotherapist also holds the role of coordinator (Appleton et al, 1997), as has been identified as a problem in previous studies (Hannigan et al, 2018;Alve et al, 2013;Nilsen & Jensen, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This difference is notable because the coordinator is assigned the responsibility for the planning and follow-up for the ISP (Norwegian Directorate of Health, 2015). The discrepancy between reporting having a coordinator and the other types of coordinating services may be substantial; however, it could also be seen an under-reporting due to unclear boundaries and overlapping roles, for instance, when the child's physiotherapist also holds the role of coordinator (Appleton et al, 1997), as has been identified as a problem in previous studies (Hannigan et al, 2018;Alve et al, 2013;Nilsen & Jensen, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interruptions were surprisingly widespread among coordination services, being identified in one-third of the families with a multidisciplinary support team, more than half of the families with an ISP and more than two-thirds of the families with a service coordinator. Previous research has revealed multiple barriers when service coordination is to be implemented in healthcare (Hannigan et al, 2018;Holum, 2012;Nilsen & Jensen, 2012). In a Norwegian context, one previously identified challenge is the ISP ultimately becoming a "desk document" instead of a "live document" (Nilsen & Jensen, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For many people in a rehabilitation process, the individual plan has proved very useful (Thommesen, Sandvin, and Normann 2003). However, recent research has proved that there are various challenges with the use of the individual plan (Alve et al 2013;Hansen 2007;Nilsen and Jensen 2012;Nilssen 2011;Røthing 2007;Slettebø et al 2012). This article will describe some unintended forms of use that are not in line with the original intentions, and illustrate how this is in accordance with international welfare trends.…”
Section: Introductionmentioning
confidence: 94%